'Aching to be a boy': A preliminary analysis of gender assignment of intersex persons in India in a culture of son preference. (3rd June 2020) - Das, Arpita
Abstract: Intersexuality,  particularly in the global South,  remains an under‐researched field of study. In my in‐progress doctoral research project,  I explore the cultural, social, and medical discourses that influence how key stakeholders such as healthcare providers make decisions about the sex and gender assignment of the intersex child in India. In this paper I interrogate some of these ideas around gender assignment of intersex people in India, paying particular attention to the context of son preference. I am interested in exploring how decisions of gender assignment by medical professionals are guided by ideas of son preference. Focusing on four qualitative, semi‐structured, in‐depth interviews across two cities with medical doctors from different specializations, this paper is a preliminary attempt to examine some of the factors that guide medical professionals in making decisions about gender assignment of intersex children and explore the dynamics of the decision‐making process. Specifically, I explore the factors that inform doctors' decision‐making and locate these decision‐making processes within the broader socio‐cultural context of India.